PERANCANGAN STRATEGI MITIGASI RESIKO PADA RANTAI PASOK RAW MATERIAL GLUCOSE DI INDUSTRI KRIMER - Romadhona, Robby Indra; Titisari, Manik Ayu (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2024)
Supply chain is a system that connects various parties in the production process from upstream to downstream with the aim that products can be delivered to consumers on time and also in the right quantity. The purpose of supply chain management is to ensure that all processes in the supply chain run efficiently, effectively and provide optimal value. The problem in the creamer industry is that the arrival schedule of glucose raw materials is often late or not according to schedule, which disrupts the production process. Efforts in risk mitigation actions can be carried out with the SCOR (Supply Chain Operation Reference) method and also HOR (House Of Risk). In the SCOR method process, there are 5 main processes, namely plan, source, make deliver and return. In the HOR phase 1 method, the results with the highest risk agent value with moderate risk are obtained, namely the raw material planning team is less careful, raw materials arrive not on schedule, and lack of coordination from the raw material planning and purchasing team. While HOR phase 2 obtained risk mitigation results in the form of ensuring the schedule of arrival of raw materials, forecasting related to raw material supplies and production needs, adding and identifying suppliers. In risk mitigation in the form of making a schedule of handling plans to carry out risk mitigation that will be carried out with a plan tailored to the conditions in the creamer industry.